2017
DOI: 10.1186/s13568-017-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

pH rather than nitrification and urease inhibitors determines the community of ammonia oxidizers in a vegetable soil

Abstract: Nitrification inhibitors and urease inhibitors, such as nitrapyrin and N-(n-butyl) thiophosphoric triamide (NBPT), can improve the efficiencies of nitrogen fertilizers in cropland. However, their effects on ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) across different soil pH levels are still unclear. In the present work, vegetable soils at four pH levels were tested to determine the impacts of nitrification and urease inhibitors on the nitrification activities, abundances and diversiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…In contrast, Nicol et al 34 found that AOB abundances significantly decreased with decreasing pH, while AOA exhibited an opposite relationship. Further, Xi et al 55 observed that a decrease in soil pH resulted in a significant increase in AOA abundances without affecting AOB abundances. The lack of major change in AOA or AOB abundances observed here could be due to the relatively small range of pH change in this study, with salinity having a more important effect.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Nicol et al 34 found that AOB abundances significantly decreased with decreasing pH, while AOA exhibited an opposite relationship. Further, Xi et al 55 observed that a decrease in soil pH resulted in a significant increase in AOA abundances without affecting AOB abundances. The lack of major change in AOA or AOB abundances observed here could be due to the relatively small range of pH change in this study, with salinity having a more important effect.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the activity, distribution and abundance of soil microbes in soils treated with NBPT, a few studies have been carried out. A very recent paper found that while NBPT did not influence the growth or ratio of ammonia oxidizers (archaea and bacteria) in vegetable soil, soil pH played a prominent role (Xi et al 2017). Another study found that application of NBPTcoated urea fertilizer reduced the decrease in soil pH otherwise observed on fertilization with un-amended urea, suggesting that use of NBPT may lessen the effect of urea fertilization on native soil microbial communities (Shi et al 2017).…”
Section: Ammonia Emission Mitigation By Urease Inhibitorsmentioning
confidence: 99%
“…This research focused on the abundance of microbial community construction and the effects of specific parameters on AOA and AOB groups along streams south of the Dabie Mountains (from upstream to downstream), China. The phylogenetic analysis of the AOA amoA communities in the rivers and sediments showed that most of the revealed sequences (90.0%-97.0%) in the nine sampling sites were linked with Nitrososphaera viennensis and Nitrosopumilus sp clusters I.2, I.3, and I.4 [24]. N. viennensis and Nitrosopumilus sp (moderately) (Figure 2) were extracted from sediments, which could autotrophically or heterotrophically, or even mixotrophically, be involved in ammonia oxidation in freshwater and sediment environments [25].…”
Section: Discussionmentioning
confidence: 99%